X(x-5))-
6=0 equações
Soluções para a tarefa
Respondido por
0
x (x - 5) - 6 = 0
x^2 - 5x - 6 =0
a= 1
b= -5
c= -6
Primeira Etapa:
Delta = b^2 - 4. a. c
Delta = (-5)^2 - 4.(1).(-6)
Delta= 25 + 24
Delta = 1
Segunda Etapa ( imagem)
x^2 - 5x - 6 =0
a= 1
b= -5
c= -6
Primeira Etapa:
Delta = b^2 - 4. a. c
Delta = (-5)^2 - 4.(1).(-6)
Delta= 25 + 24
Delta = 1
Segunda Etapa ( imagem)
Anexos:
![](https://pt-static.z-dn.net/files/d9b/d929d07add94fb8cb27f051af15c561d.jpg)
Perguntas interessantes
Matemática,
11 meses atrás
Matemática,
11 meses atrás
Geografia,
11 meses atrás
Geografia,
1 ano atrás
Português,
1 ano atrás
Português,
1 ano atrás
Sociologia,
1 ano atrás
Filosofia,
1 ano atrás